2021
DOI: 10.1039/d0sc05900e
|View full text |Cite
|
Sign up to set email alerts
|

Selective cleavage of unactivated arene ring C–C bonds by iridium: key roles of benzylic C–H activation and metal–metal cooperativity

Abstract: The detailed mechanism of iridium-mediated C–C cleavage in unactivated arenes reveals the key factors enabling the process and helps predict the scope of the cleavage reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…We conducted all geometry optimizations, reaction path calculations and calculations of thermodynamic corrections with the B3LYP functional and a mixed basis set of LANL2DZ for Ir and 6-31G(d) for all other atoms, which gave excellent results for the calculations of C-C oxidative addition in η 4 -arene iridium complexes. 20 The DFT computations indicated that the benzylic C-H activation 11→6 (Fig. 5, green path) has indeed the lowest energy as compared to the aromatic C-H activation 11→ 17 (Fig.…”
Section: Irmentioning
confidence: 95%
See 1 more Smart Citation
“…We conducted all geometry optimizations, reaction path calculations and calculations of thermodynamic corrections with the B3LYP functional and a mixed basis set of LANL2DZ for Ir and 6-31G(d) for all other atoms, which gave excellent results for the calculations of C-C oxidative addition in η 4 -arene iridium complexes. 20 The DFT computations indicated that the benzylic C-H activation 11→6 (Fig. 5, green path) has indeed the lowest energy as compared to the aromatic C-H activation 11→ 17 (Fig.…”
Section: Irmentioning
confidence: 95%
“…During our investigation of arene C-C cleavage in rare Cp*Ir(η 4 -arene) complexes, 18,19 we found that thermolysis of the mesitylene complex in the presence of PMe 3 does not lead to C-C cleavage, but cleanly affords a product of benzylic C-H activation, Cp*Ir(CH 2 C 6 H 3 Me 2 -3,5)(PMe 3 ). 20 This selective benzylic C-H activation, however, could be explained by the steric hindrance of aromatic C-H bonds. To test if benzylic C-H activation would occur in the least sterically hindered methylarene, toluene, we heated the iridium complex Cp*Ir(η 4 -toluene) (1) in the presence of 4 equiv.…”
mentioning
confidence: 99%
“…[17][18][19][20][21] However, nitrogen atom insertion into the aromatic carbocyclic skeleton is still difficult because of the inherent inertness of the carbon-carbon bonds of aromatic rings. [22][23][24][25] N-Heterocycles present the unique class of cyclic structural frameworks present in various natural and non-natural products. Big data analytics reveal that heterocycle formation has been one of the most frequently used reactions in medicinal chemistry over the past several decades.…”
Section: Introductionmentioning
confidence: 99%
“…In the past several decades, d-block transition metals have been widely used to catalyze hydrocarbon reactions. The catalytic behavior of transition metals is highly sensitive to their electron configurations, oxidation states, and surface absorptivity . Among these factors, the electron configuration of the metal atom plays a central role in the C–C and C–H bond activation. This is because the metal–ligand reactions involve favorable metal–ligand orbital interactions and electron transfer that minimize the activation barrier of C–C and C–H bond dissociation. ,, An effective way for manipulating electronic configurations of the metal atom is by selectively exciting the metal atom to an excited state and then carrying out an excited-state metal–ligand reaction.…”
Section: Introductionmentioning
confidence: 99%